2023
DOI: 10.1002/anbr.202300082
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters for Tumor Diagnosis and Treatment

Shiqun Chen,
Shasha Li,
Yili Wang
et al.

Abstract: Nanomedicine shows remarkable potential to improve the efficacy of diagnosis and treatment of tumors, utilizing nanotechnologies and nanomaterials. Gold nanoclusters (AuNCs) have emerged as a highly promising option due to their exceptional optical and enzyme‐mimicking catalytic activities as well as good biocompatibility. The renal clearable clusters can enrich in the tumors upon their enhanced permeability and retention properties, which benefits the tumor‐related applications. The fluorescence of AuNCs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 167 publications
0
3
0
Order By: Relevance
“…Urine fluorescence imaging and fluorescence quantification showed that urinary excretion of the Au NCs was 75%, indicating that the high-dose clusters have excellent renal clearance (Figure h,i). High doses of clusters exhibited a high renal clearance, which may contribute to the normal physiological response of the body. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine fluorescence imaging and fluorescence quantification showed that urinary excretion of the Au NCs was 75%, indicating that the high-dose clusters have excellent renal clearance (Figure h,i). High doses of clusters exhibited a high renal clearance, which may contribute to the normal physiological response of the body. ,, …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the gold clusterzymes can be endowed with strong fluorescence and high catalytic activities simultaneously via precise structural regulation . With good biocompatibility, the gold clusterzymes show promising prospects in clinical translation. …”
Section: Introductionmentioning
confidence: 99%
“…More recently, AuNCs have attracted much interest in biosensing applications [131][132][133][134]. Compared with semiconductor quantum dots or other metal NDs, AuNCs possess several distinct features, such as photophysical/chemical properties, good stability, and excellent biocompatibility [135][136][137][138][139][140][141][142]. Several studies utilized AuNCs for the construction of differential sensing strategies [72,[143][144][145].…”
Section: Differential Sensing Based On Gold Nanoclusters (Auncs)mentioning
confidence: 99%